2008
DOI: 10.1186/1471-244x-8-71
|View full text |Cite
|
Sign up to set email alerts
|

Acute maternal stress in pregnancy and schizophrenia in offspring: A cohort prospective study

Abstract: Schizophrenia has been linked with intrauterine exposure to maternal stress due to bereavement, famine and major disasters. Recent evidence suggests that human vulnerability may be greatest in the first trimester of gestation and rodent experiments suggest sex specificity. We aimed to describe the consequence of an acute maternal stress, through a follow-up of offspring whose mothers were pregnant during the Arab-Israeli war of 1967. A priori, we focused on gestational month and offspring's sex. Method:In a pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
112
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(118 citation statements)
references
References 44 publications
(59 reference statements)
1
112
0
5
Order By: Relevance
“…Recent studies also indicate a higher prevalence of posttraumatic stress, anxiety and depression, and affective disorders in adults who were born in Jerusalem between 1964 and 1976, whose mothers were subject to war stress in the first quarter, especially in the third month of pregnancy 14 . The work of Malaspina et al 15 also shows that the mother's gestational stress caused by the Arab-Israeli war in 1967 in the first quarter turned out to represent a significant risk factor for schizophrenia, more often in females. Feldman and Vengrober 10 established the diagnosis of posttraumatic stress disorder in 37.8% of children aged 1.5 to 5 subject to the war in the Gaza Strip, while Meijer 16 proved the connection between the wartime stress and psychiatric disorders, including children's regressive, non-affiliative and dissocial behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also indicate a higher prevalence of posttraumatic stress, anxiety and depression, and affective disorders in adults who were born in Jerusalem between 1964 and 1976, whose mothers were subject to war stress in the first quarter, especially in the third month of pregnancy 14 . The work of Malaspina et al 15 also shows that the mother's gestational stress caused by the Arab-Israeli war in 1967 in the first quarter turned out to represent a significant risk factor for schizophrenia, more often in females. Feldman and Vengrober 10 established the diagnosis of posttraumatic stress disorder in 37.8% of children aged 1.5 to 5 subject to the war in the Gaza Strip, while Meijer 16 proved the connection between the wartime stress and psychiatric disorders, including children's regressive, non-affiliative and dissocial behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, environmental factors have been demonstrated to contribute to the disease in humans (Vereczkei and Mirnics, 2011). Specifically, fetal hypoxia (Mittal et al, 2008), maternal stress (Malaspina et al, 2008;Van Os and Selten, 1998), and adolescent cannabis exposure (Caspi et al, 2005), to name a few, are risk factors for schizophrenia. It should be noted that rearing conditions of the F2 offspring may contribute to their schizophrenia-like phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Death of spouse 31,32 and experience of catastrophic events, such as war 33 and nuclear explosion, 34 have been found to increase the risk of schizophrenia among those exposed. van Os and Selten 33 found an increased relative risk (RR) of schizophrenia (RR 1.28) among those in the Netherlands who were in their first or second trimester during the Nazi invasion in May 1940, and Malaspina and colleagues 35 found that those in their second month of gestation during the 1967 Arab-Israel War (Six-Day War) also had an increased risk of schizophrenia. Imamura and colleagues 34 found that those exposed in their second or third trimester to the nuclear explosion in Nagasaki were at increased risk of schizophrenia.…”
Section: Prenatal Stressmentioning
confidence: 99%